365 of Henry Ford's sayings / [compiled by P.M. Martin]. - Ford, Henry, 1863-1947. (Tufts University. Tisch Library., 2019)
1 online resource (46 pages); Cover title.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2018. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.